A Multiyear Record of Rainfall and Ionic Composition along an Elevation Gradient in Northeastern Puerto Rico - Elvis Torres-Delgado; Grizelle González; Ernesto Medina; María M. Rivera (Aerosol and Air Quality Research)
Abstract This study analyzes multiyear data recorded by 21 stations along an elevation gradient (0–1045 m a.s.l.) in the Luquillo Mountains on the rainfall and the rainwater chemistry. The total ionic concentration and the rainwater volume exhibited an inverse exponential relationship, with the correlation coefficients ranging from –0.66 to –0.90. Furthermore, the rainfall tended to increase with the elevation, although a few stations, owing to their geographical location and their exposure to the prevailing winds, departed from this trend. The ionic composition also displayed clear seasonality: Contributions from African crustal aerosols and, to a lesser degree, North American anthropogenic aerosols were observed during summer and winter, respectively, whereas marine aerosols were influential year-round. Finally, the annual loads (kg ha−1 y−1) first increased for all of the species, except PO43– and K+, from the lowland to the cloud formation levels (by 47–121%) and then decreased for all of them, except PO43– and NO3−, at the altitudes above.